Art-175 Is a Highly Efficient Antibacterial against Multidrug-Resistant Strains and Persisters of Pseudomonas aeruginosa - Briers, Yves; Walmagh, Maarten; Grymonprez, Barbara; Biebl, Manfred; Pirnay, Jean-Paul; Defraine, Valerie; Michiels, Jan; Cenens, William; Aertsen, Abram; Miller, Stefan; Lavigne, Rob (Antimicrobial agents and chemotherapy, 2014)
Artilysins constitute a novel class of efficient enzyme-based antibacterials. Specifically, they covalently combine a bacteriophage-encoded endolysin, which degrades the peptidoglycan, with a targeting peptide that transports the endolysin through the outer membrane of Gram-negative bacteria. Art-085, as well as Art-175, its optimized homolog with increased thermostability, are each composed of the sheep myeloid 29-amino acid (SMAP-29) peptide fused to the KZ144 endolysin. In contrast to KZ144, Art-085 and Art-175 pass the outer membrane and kill Pseudomonas aeruginosa , including multidrug-resistant strains, in a rapid and efficient (∼5 log units) manner. Time-lapse microscopy confirms that Art-175 punctures the peptidoglycan layer within 1 min, inducing a bulging membrane and complete lysis. Art-175 is highly refractory to resistance development by naturally occurring mutations. In addition, the resistance mechanisms against 21 therapeutically used antibiotics do not show cross-resistance to Art-175. Since Art-175 does not require an active metabolism for its activity, it has a superior bactericidal effect against P. aeruginosa persisters (up to >4 log units compared to that of the untreated controls). In summary, Art-175 is a novel antibacterial that is well suited for a broad range of applications in hygiene and veterinary and human medicine, with a unique potential to target persister-driven chronic infections.